The use of African music in the church - Louw, Johan K. (International Library of African Music, 1956)
After my short experience of work amongst African people in Nyasaland—because I admit that 14 years is not a very long period—I am becoming more and more convinced that the foreignness of the music we use in worship is a very important contributant factor in making the Christian religion to be something Western in the mind of many an African. There is, as far as I can judge, a translation of the Bible in the Nyanja language, which is, in many ways, a very admirable translation. So much of the life of the people we meet in the Bible is more like that of the people of the Country of the Lake than like that of modern Westerners that the Bible speaks to the Nyanja reader and makes its own appeal to his mind and heart. Some attempts have been made recently to bring our forms of worship closer to the life of the people, though much more may need to be done. But in this most important field of music very nearly nothing has been done with regard to the hymnbook used at present.
Keywords: African Music